Studi Penafsiran Makna Khusyuk dalam Al-Qur’an Perspektif Tafsir Al-Maraghi - Taubah, Annisa; Rohkani, Siti; Astuti, Indri (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2024)
This study reviews the meaning of khusyuk in the Perspective Tafsir Al-Maraghi. This Tafsir is one of the most monumental contemporary interpretations of this century, a language that is effective and easy to understand for the entire community, at the same time very relevant to this research. The purpose of this research is to analyze the meaning of khusyuk in Tafsir Al-Maraghi and its implications in real life by using the method of library research or research of the library. The results of the analysis show that the meaning of khusyuk is the use of the heart, submission, tenderness, calm, and presence when doing obedience to God, followed by the entire body, both visible and invisible. Among them are those who believe in the meeting with their Lord on the Day of Judgment, those who weep for fear of Allah, and those who soften their hearts when the Quran is recited to them. So that from it will be born obedience and submission to Him, His reward and joy, and the birth of faith.